Kinematic differences in finger joints based on archery shooting scores - Ryu, S.; Kim, J.-H.; Kim, D.-K.; Yoon, S. (Korean Journal of Sport Biomechanics, 2024)
Objective: The purpose of this study was to investigate the kinematic differences in the upper limb and finger joints during archery shooting based on the score, and to analyze the effect of finger joint movement on the score. Method: The study participants consisted of 6 female athletes (Age: 20.0 ± 0.9 years, Height: 162.8 ± 6.7 cm, Body weight: 56.2 ± 5.8 kg, Career: 10.0 ± 1.5 years). The participants shot a total of 15 arrows (3 arrows per round, 5 rounds), simulating conditions like an actual archery competition. The data for trials scoring 10, 9, and 8 points were analyzed, with 2 attempts for each score. The shooting phase and release phase were selected for analysis. The variables were the joint angles of the upper limb and finger joints. Statistical analysis was conducted using one-way repeated measures ANOVA and multiple regression analysis. Results: First, the range of motion (ROM) in the metacarpophalangeal (MCP) joint of the ring finger was significantly greater in the 8-point trials compared to the 9-point and 10-point trials (p<.05). Second, the ROM of the ring finger's MCP joint was found to negatively affect the archery score (p<.05). Conclusion: Based on these findings, it is crucial to precisely control the small movements of the finger joints to achieve higher scores in archery. Furthermore, minimizing finger joint movement is essential to maintain shooting consistency.